Народ слабый духом может быть уничтожен - Кадиевская, И.А. (Культура народов Причерноморья, 2014)
Актуальность изучения силы народного духа обусловлена активизировавшимися процессами дегуманизации общества. Результатом кризисных явлений последнего времени явилась деформация общественного сознания, сопровождающаяся падением уровня духовности населения. Повышение силы духа нашего народа является залогом его дальнейшего устойчивого развития. Поэтому социально-философское осмысление значения силы народного духа является актуальным и научно значимым. В статье проанализирован такой социальный фактор как духовность. Рассмотрено понятие «духовная сила народа». Выделены особенности духовных качеств украинского народа. Актуальність вивчення сили народного духу обумовлена активізацією процесів дегуманізації суспільства. Результатом кризових явищ останнього часу стала деформація суспільної свідомості, яка супроводжується падінням рівня духовності населення. Підвищення сили духу нашого народу є запорукою його подальшого стійкого розвитку. Тому соціальнофілософське осмислення значення сили народного духу є актуальним і науково значущим. В статті проаналізований такий соціальний фактор як духовність. Розглянуто поняття «духовна сила народу». Виділені особливості духовних якостей українського народу. The urgency of the study of the force of people spirit is caused by the activated processes of the dehumanization of society. The deformation of public consciousness, which is accompanied by a drop in the level of the spirituality of population, was the result of the crisis phenomena of last time. An increase in the force of the spirit of our people is the guarantee of its further steady development. Therefore the social- philosophical comprehension of the value of the force of people spirit is immediate and scientifically significant. In the article is analyzed most important the social factor, which determines state and nature of the development of public consciousness as spirituality, spiritual state. It is established that in the contemporary society the transformation of the highest intellectual values of humanism, love, good, truth, beauty, freedom and validity occurs. The regeneration of authentic spirituality into the quasi-spirituality as a result is observed. Is examined concept “spiritual force of people”. The spiritual force of people in many respects depends on a sense of self-respect. Self-esteem to capably inspire, to help to surmount difficulty, to direct in the achievement of the objective. The humiliation of the merit of people leads to weakening of spiritual resources, to not the desire and not the ability to be developed and to live complete life. The special features of the spiritual qualities of Ukrainian people are isolated.